Pengaruh Pengembangan Karir, Promosi, Loyalitas, dan Lingkungan Kerja terhadap Kinerja Pegawai Sekretariat DPRD Kepulauan Riau - Suigwan Suigwan; Sumardin Sumardin; Sabri Sabri (Asosiasi Ide Bahasa Kepri, 2026)
This study aims to analyze the influence of career development, promotion, employee loyalty, and work environment on employee performance at the Secretariat of the Regional House of Representatives (DPRD) of the Riau Islands Province. Human resource management plays a strategic role in enhancing organizational effectiveness, particularly within public sector institutions that require high levels of professionalism and service quality. This research employed a quantitative explanatory approach using a survey method. The population consisted of all employees of the Secretariat of the DPRD of the Riau Islands Province, totaling 71 employees, and a saturated sampling technique was applied, resulting in all employees being included as respondents. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS. The findings reveal that career development, promotion, employee loyalty, and work environment each have a positive and significant effect on employee performance. Career development significantly enhances employees’ competencies and motivation, while promotion serves as a mechanism for recognizing performance and increasing job responsibility. Employee loyalty contributes to organizational commitment and work dedication, whereas a conducive work environment supports productivity and employee well-being. Simultaneously, the four independent variables significantly influence employee performance, as indicated by an F-value of 120.798, which exceeds the critical value, confirming the robustness of the proposed model. The study concludes that improving employee performance in public organizations requires integrated human resource policies that emphasize career advancement opportunities, fair promotion systems, loyalty enhancement programs, and supportive work environments. These findings provide practical implications for policymakers and organizational leaders in strengthening human resource management practices within government institutions.